Empirical Findings on Learning Success and Competence Development at Learning Factories: A Scoping Review - Nine Reining; Simone Kauffeld (Education Sciences, 2022)
To meet the changing competence requirements for employees in engineering professions, education and training need to adapt accordingly. Learning factories offer various possibilities to design or integrate practice-oriented learning into training measures. Whether this approach in fact facilitates learning and competence development is rarely investigated. For this reason, the objective of this scoping review is to analyze and summarize the existing empirical findings on learning success and competence development in learning factories regarding their evaluation methods and results. Following standardized guidelines (PRISMA, JBI) for scoping reviews, 12 databases were researched. The literature screening led to the identification of 24 publications included in the final analysis. The results indicate that a variety of evaluation methods are used to assess learning and competences at learning factories and that criteria of all four competence facets (professional, methodological, social, and self-competence) can be enhanced at learning factories in general. As many of the identified studies show potential for improvement regarding the quality of the used methods and analysis of results, further studies on these topics are needed. Evaluations should be integrated into all training measures at learning factories to ensure learning success and competence development and to be able to readjust design, structure, and didactics where necessary.